Comparative Evaluation of Root Resorption During Canine Retraction Using Segmental T-Loop and Geometry-X: A CBCT-Based Split-Mouth, Randomized Clinical Trial - Dr. Shashank Jain,Dr. Amitabh Kallury,Dr. Rajesh Kumar Balani,Dr. Akshay Agarwal,Dr. Shambhavi Shukla,Dr. Shounak Banerjee (South Eastern European Journal of Public Health, 2025)
Aim: To compare the extent of root resorption during canine retraction using Segmental T-loop and Geometry-X, evaluated through CBCT imaging. Materials and Methods: Patients with Angle’s Class I malocclusion and anterior crowding, requiring first premolar extraction, were treated with Segmental T-loop and Geometry-X mechanics on opposite sides of the maxillary/mandibular arch in a split-mouth design. Root resorption was assessed by comparing pre-treatment and post-canine retraction CBCT scans for each technique. Results: The Geometry-X technique resulted in a mean root resorption of 0.76 mm, whereas the Segmental T-loop technique showed a higher mean resorption of 1.08 mm. Although this suggests that the Segmental T-loop technique may cause more root resorption compared to the Geometry-X technique, statistical analysis indicated that the difference between the two techniques was not significant. Conclusion: The Segmental T-loop technique demonstrated slightly higher root resorption compared to the Geometry-X. However, the differences between the two methods were not statistically significant. This indicates that both techniques may have a similar impact on canine root integrity.